A study on automated toll collection: towards the utilisation of RFID-based system. (18th February 2022) - Kannan, Naresh; Goyal, Ranjan; Goel, Dhruv; Anitha, K.
The toll collection is becoming a major problem on the highways leading to large waiting queues. Toll gates installed on highways result in increased waiting time and fuel usage. In this paper, a study on automated toll collection system using radio frequency identification (RFID)-based system is presented, which provides fast identification of vehicles and toll collection. Using this system, the identification can be done just by slowing down the speed of the vehicle when it is passing from the toll plaza. The RFID reader scans the RFID tag or card and deducts the amount from it. The research analysed the system by proposing a mechanism and implementing an example scenario, which considered the random arrival of different vehicles. This technique is also compared with other existing mechanisms such as number plate recognition and barcode-based passes, which showed the need to utilise this technique for toll collection.